Flightless litter-dwelling Cotasterosoma (Coleoptera: Curculionidae: Cossoninae) found outside of Japan, with mtDNA phylogeography of a new species from Southwest China - Grebennikov, Vasily V.; Morimoto, Katsura (Zootaxa, 2016)
The herein reported beetles (Figs 1, 2) were repeatedly sampled by the first author since 2008 by sifting leaf litter in two forested localities in Southwest China: Cang Shan Mountain Range in Yunnan and Mount Emei in Sichuan (Fig. 3). The specimens’ characteristic appearance and edaphic way of life were consistent with those of various members of the subfamily Cossoninae (Morimoto 1973, 1993, 1995), although a more precise taxonomic assignment remained elusive. In 2015 the second author saw images of these beetles and suggested their affinities to the genus Cotasterosoma Konishi, 1962. This taxon until present was known from a single specimen collected in 1954 in Shikoku, Japan, and illustrated in Morimoto (1993), although additional congeneric specimens are known to the second author. The purpose of this paper is to document our discovery of the genus in Southwest China by describing a new species, illustrating its external and genital morphological characters, releasing DNA barcode data and providing phylogeographic interpretations of our findings.